Christian-holistic teaching as an instrument to combat reductionism in education - Christiaan van Olst, Peter (International journal of Christianity & education, 2023)
Cultural change and global pluralism are causing an increasing plea for Christian-holistic education. However, this term lacks clear definition based on a proper description of the cultural background that provoked it. A secular definition of holistic education is taken from a worldwide movement for Whole Child Development and compared with the culture-critical thinking of three visionaries from the Christian tradition. This leads to the definition that Christian-holistic education seeks all dimensions of human development, aiming at the heart as the undivided principle of its existence, placing it with pedagogical optimism before God to seek its restoration and longing to serve.